Hemisynthesis and Spectroscopic Characterization of Two Novel O-Allylated Benzophenones from Garcinia punctata Oliv. (Clusiaceae) - Ngameni1, B.; Fotso2, G.W.; Ngachussi2, E.; Poumale Poumale2, H.M.; Ngadjui2, B.T.; Shiono3, Y.; Murayama3, T. (Asian Journal of Chemistry, 2014)
Four known natural compounds i.e., (-) isogarcinol, (+) 7-epigarcinol, stigmasterol and b-sitosterol-3-O-b-D-glucoside were isolated from the stem bark of Garcinia punctata oliv. From (-) isogarcinol, two new hemisynthesis O-allylated benzophenones were synthesized using allylbromide in the presence of potassium carbonate in anhydrous acetone. The structural elucidation of all the compounds was done by mass spectrometry, IR, 1D- and 2D-NMR analysis and also by comparison with previous reports. This is the first study to report on the one step allylation of the natural (-) isogarcinol using the base catalysis conditions.